EKSPLORASI STUDI WISATA RELIGI: ETNOMATEMATIKA PADA MAHA VIHARA MAITREYA DI CEMARA ASRI MEDAN: Exploration of Religious Tourism Studies: Ethnomathematics at the Maitreya Maha Vihara in Cemara Asri Medan - Rahmah, Atika; Salsabila, Avita; Nasution, Afifah Nabila; Ningsih, Sri Rahayu; Syahrani, Zulayli; Andhany, Ella (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
Mahavihara Maitreya in Cemara Asri Medan Complex is one of the largest monasteries in Indonesia and is known as a religious tourism destination that can attract tourists from various backgrounds to see and understand the richness of typical Buddhist architecture. The study of ethnomathematics at Maha Vihara Maitreya can provide benefits, both for academics, tourists, and the general public who want to understand the relationship between mathematics, culture, and spirituality. The research method used in this study is a qualitative method with an ethnographic approach. This type of research is field research, namely research that is carried out systematically to collect data directly in the field. The data collection instrument in this study is by means of observation and documentation. The conclusion based on the results and discussion, this study shows that the exploration of religious tourism and ethnomathematics at Maha Vihara Maitreya not only provides a new perspective in the study of mathematics, but also enriches the understanding of the ways in which culture and religion integrate science in their lives, which in turn increases the educational value and tourism experience for visitors.